2016
DOI: 10.3390/su8040327
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Leadership Practices Driving Financial Performance: Empirical Evidence from Thai SMEs

Abstract: Many managers and researchers alike are asking: What does an enterprise need to do to generate a proper balance between economic, social, and ecological objectives while gaining superior corporate financial performance, resilience, and sustainability? Several leadership concepts for enhancing organizational sustainability have emerged in recent years, but none provides an integrative approach, with the exception of Sustainable Leadership (SL). However, empirical research examining the effects of various SL pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 62 publications
10
96
1
2
Order By: Relevance
“…Neither Lean and Nguyen (), who built a market model, nor Suriyankietkaew and Avery (), who used a survey in order to build his variable, defined specific economic variables in the construction of their papers.…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither Lean and Nguyen (), who built a market model, nor Suriyankietkaew and Avery (), who used a survey in order to build his variable, defined specific economic variables in the construction of their papers.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Wang and Sarkis () suggested using variables that might cover economic, financial, and organizational performance to enrich the research, whereas other authors suggested using market variables combined to control variables (Lassala et al, ) and the indebtedness ratio, company size, value generation, and other control variables (Santis et al, ; Siew et al, ; Suriyankietkaew & Avery, ).…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We develop a multilevel theoretical and empirical model that proposes both main and interactive effects of transformational CLTs and sustainability of societies on individual level social entrepreneurship. We add to literature examining the interface of leadership and sustainability [25]. Our findings add to the increasing scholarship that apply inputs from institutional theory to explore and understand phenomenon at the crossroads of business and society [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability at the workplace should go beyond social and environmental responsibility and should include all management processes that aim at creating long-term well-being [2]. To develop a sustainable workplace, leaders are needed that engage in leadership behavior aimed at supporting the health of their employees in the long term [1].…”
Section: Introductionmentioning
confidence: 99%